Kekaburan Dalam Perjanjian Waralaba - Nababan, Nancy Eclesia; M.T.V.M, Sri Maharani; Sutrisno, Sutrisno (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2025)
The dynamics of business development in the current era have marked franchising as a very effective strategy for business owners to expand their reach with a high level of cost efficiency. In facing market complexity and dynamics, the franchise business model has become the main choice for many business actors. Within this framework, this study explores the specific case of a franchise located in